Mucin 4 Immunosensor Based on p-aminophenylacetic Acid Grafting on Carbon Electrodes as Immobilization Platform. (2017) - Hosu, Oana; Tertiş, Mihaela; Melinte, Gheorghe; Săndulescu, Robert; Cristea, Cecilia
Abstract: A simple impedimetric label-free immunosensor was developed for the specific and sensitive detection of mucin 4 (MUC 4) protein by using graphite based screen printed electrodes modified with an aryl diazonium salt or compound ( p - aminophenylacetic acid) for the immobilization of antibody anti-MUC4 via amidic bond. Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) were used in order to characterize and optimize the electrografting process. The parameters involved in each step of the immunosensor design were optimized. The performance of the immunoassay in terms of sensitivity, reproducibility and selectivity was studied.